PROBLEMATIKA HUTANG PADA MASA PANDEMI COVID-19 DI DESA SUKAWANGI - Suud Sarim Karimullah; Lilyan Eka Mahesti (Jurnal Asy-Syukriyyah, 2021)
This research will look at how debt problems during the pandemic of Covid-19 in community life in Sukawangi village towards family harmony. This is because debt can be a helper for a family afflicted with economic problems, but on the other hand, debt can also ensnare and torment a family which results in conflicts over the harmony and integrity of the household. This research is a type of field research with the nature of analytic descriptive research, which provides an overview and explanation of the facts of situations, circumstances and social phenomena that occur in the field through an anthropological approach. In this research, data collection methods will be carried out through interviews, observation and analysis of various documentation. The results of this study concluded that the economic dependence of the Sukawangi village community on debt during the pandemic of Covid-19 to survive caused problems in family life. Few people are successful and successful in managing their money from debt by making good economic breakthroughs.